A framework for distributed manufacturing applications - Leitão, Paulo (2010)
The new organisational structures used in world wide manufacturing systems require the development of distributed applications, which present solutions to their requirements. The work research in the distributed manufacturing control leads to emergent paradigms, such as Holonic Manufacturing Systems (HMS) and Bionic Manufacturing Systems (BMS), which translates the concepts from social organisations and biological systems to the manufacturing world. This paper present a Framework for the development of distributed manufacturing applications, based in an agent-based architecture, which implements some Holonic and Bionic Manufacturing Systems concepts.